ID 80 – Comparison of surface recording and near nerve technique in diagnosis and localization of ulnar nerve entrapment neuropathy. Issue 3 (March 2016) - Fuchs, S.; Otto, M.; Qerama, E.; Beniczky, S.; Johnsen, B.; Fuglsang-Frederiksen, A.; Tankisi, H.
Abstract : Objective: To investigate whether surface electrodes is comparable to near nerve technique (NNT) in diagnosing and localizing the ulnar neuropathy. Methods: Forty-five patients, referred consecutively with the suspicion of ulnar nerve entrapment neuropathy were prospectively included. The patients underwent first the routine examination using NNT. Then, another physician blinded to the results of the former examination with NNT, repeated the study using surface electrodes. Results: In 38 of 45 patients (84%), both methods showed similar results, from which in 16 patients NCSs were normal and in 22 abnormal. Surface electrode technique showed normal results while NNT was abnormal in 4 patients and vice versa in 3. In 23 of 29 patients (79%) having abnormal NCSs with either surface electrodes or NNT, one or both methods showed localisation of the neuropathy to the elbow, all of these 23 patients could be localized by NNT and only 14 of them (60%) by surface electrodes. Conclusion: Surface electrodes technique is comparable to NNT in showing whether there is abnormality or not. However, localisation of entrapment neuropathy is more likely with NNT. Key massage: Surface electrodes may be used to screen the patients. Further studies with higher number of patients have to be conducted.